Critical Role of TFEB-Mediated Lysosomal Biogenesis in Alcohol-Induced Pancreatitis in Mice and HumansSummary - Shaogui Wang; Hong-Min Ni; Xiaojuan Chao; Xiaowen Ma; Thomas Kolodecik; Robert De Lisle; Andrew Ballabio; Pal Pacher; Wen-Xing Ding (Cellular and Molecular Gastroenterology and Hepatology, 2020)
Background & Aims: Alcohol abuse is the major cause of experimental and human pancreatitis but the molecular mechanisms remain largely unknown. We investigated the role of transcription factor EB (TFEB), a master regulator of lysosomal biogenesis, in the pathogenesis of alcoholic pancreatitis. Methods: Using a chronic plus acute alcohol binge (referred to as Gao-binge) mouse model, we analyzed pancreas injury, autophagic flux, zymogen granule removal, TFEB nuclear translocation and lysosomal biogenesis in GFP-LC3 transgenic mice, acinar cell-specific Atg5 knockout (KO) and TFEB KO mice as well as their matched wild type mice. Results: We found that Gao-binge alcohol induced typical features of pancreatitis in mice with increased serum amylase and lipase activities, pancreatic edema, infiltration of inflammatory cells, accumulation of zymogen granules (ZGs) and expression of inflammatory cytokines. While Gao-binge alcohol increased the number of autophagosomes, it also concurrently inhibited TFEB nuclear translocation and TFEB-mediated lysosomal biogenesis resulting in insufficient autophagy. Acinar cell-specific Atg5 KO and acinar cell-specific TFEB KO mice developed severe inflammatory and fibrotic pancreatitis in both Gao-binge alcohol and control diet-fed mice. In contrast, TFEB overexpression inhibited alcohol-induced pancreatic edema, accumulation of zymogen granules and serum amylase and lipase activities. In line with our findings in mice, decreased LAMP1 and TFEB nuclear staining were also observed in human alcoholic pancreatitis tissues. Conclusions: our results indicate that TFEB plays a critical role in maintaining pancreatic acinar cell homeostasis. Impairment of TFEB-mediated lysosomal biogenesis by alcohol may lead to insufficient autophagy and promote alcohol-induced pancreatitis.